Re-Branding Logo Sebagai Upaya Peningkatan Daya Saing Usaha Pada UMKM Dapur 68 Di Kelurahan Klampis Ngasem - Niazi, Talitha Naila; Tondang, Ika Sari (Universitas Gajah Putih, 2023)
Micro, Small and Medium Enterprises (MSMEs) are business activities carried out by individuals or groups that aim to prosper individuals and groups. The KKN-T team identified that one of the problems lies in the lack of branding on the products being marketed, one of which is the problem of rebranding the MSMEs Kitchen 68 logo, namely not having knowledge about branding, not having a good entrepreneurial spirit and what is no less important is still not getting assistance related to technical strategy. branding for MSMEs. The purpose of branding is to introduce a product or to the wider community, build public trust in a product, and to form public perceptions of a product being sold. The function of branding is as a means of instilling a positive image in the minds of consumers, so that it needs to be understood by MSMEs actors. The method used in this activity is to use the mentoring method. The steps taken include observation, mentoring and logo creation. Based on the problems described above, it is therefore very important for community service activities to be carried out for MSMEs Kitchen 68 actors in Klampis Ngasem Village, Surabaya in re-branding the logo.